1992
DOI: 10.1128/jcm.30.1.67-73.1992
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an avianlike group A rotavirus from a calf with diarrhea

Abstract: An atypical group A rotavirus (993/83) was isolated from a 3-day-old German calf with diarrhea. It differed from 35 conventional German bovine rotavirus isolates analyzed previously with respect to subgroup (strain 993/83 was non-subgroup I and non-subgroup II), serotype (strain 993/83 showed a two-way cross-reaction with serotype 7 and a one-way cross-reaction with serotype 3), and electropherotype (strain 993/83 showed comigrating gene segments 10 and 11). Isolate 993/83 reacted with only one of four monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 40 publications
2
35
0
1
Order By: Relevance
“…Recently, it has been suggested that ARVs can also cause runting and stunting syndrome in poultry (Otto et al 2006). Typically, the ARV belongs to groups D, F, and G (McNulty 2003;Villarreal et al 2006) but those belonging to group A have been considered a major threat (Brussow et al 1992;Sugiyama et al 2004;Villarreal et al 2006). In contrast to the disease in domestic animals, the older birds can also be susceptible like the young ones, and turkeys have been the major sufferers when compared to chickens (Yason and Schat 1987).…”
Section: Disease In Other Domestic Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been suggested that ARVs can also cause runting and stunting syndrome in poultry (Otto et al 2006). Typically, the ARV belongs to groups D, F, and G (McNulty 2003;Villarreal et al 2006) but those belonging to group A have been considered a major threat (Brussow et al 1992;Sugiyama et al 2004;Villarreal et al 2006). In contrast to the disease in domestic animals, the older birds can also be susceptible like the young ones, and turkeys have been the major sufferers when compared to chickens (Yason and Schat 1987).…”
Section: Disease In Other Domestic Animalsmentioning
confidence: 99%
“…Similarly, pet animals like cats and dogs may also excrete BRV, and are thought of having role in propagation of BRV (Schwers et al 1982). Much later, in an interesting observation, a BRV isolate has been noticed to differ from other mammalian isolates during probe analysis, but got hybridized to genome of an ARV strain, thus representing a classical candidate for a natural interspecies transmission between different classes of vertebrates (Brussow et al 1992). Apart from bovines, interspecies transmission of ARVs to experimental animals has also been reported (Rohwedder et al 1995;Mori et al 2001).…”
Section: Inter-species Transmission Of Rotavirusesmentioning
confidence: 99%
“…Calf diarrhea, one of the most widespread diseases, is a complex syndrome with a complex etiopathogenesis, causing important economic losses due to morbidity and mortality, treatment costs, and reduced growth rates in affected calves (Garaicoechea et al 2006;Reidy et al 2006). The etiology of this syndrome involves infectious agents (viruses, bacteria, and protozoa) and also noninfectious factors such as herd management, host nutritional, and immunological condition which affect the outcome of the disease (Brussow et al 1992;Maes et al 2003;Garaicoechea et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Group A Rotaviruses, as the member of Reoviridae family, have clearly been established as causing significant diarrheal disease in infants and in the young of various mammalian and avian species (Brussow et al 1992;Murphy et al 1999;Flint et al 2000;Estes and Kapikian 2001).Group A bovine rotavirus (BRV) is considered the major cause of severe diarrhea in calves worldwide (Garaicoechea et al 2006). Coronaviruses as the member of Coronaviridae family are associated with economically important diseases in cattle, poultry, pigs, and cats (Lai et al 2007;Acheson 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Viruses classified as group A rotavirus (RV-A), including BoRV-A, possess two independent neutralization antigens, namely, VP4 and VP7, on the outer capsid, that specify the P type (for proteasesensitive protein) and G type (for glycoprotein), respectively (Estes, 2001;Kapikian et al, 2001). To date, six P types (P6[1], P7 [5], P8[11], P11[14], P[17], and P [21]) and 8 G types (G1, G3, G5, G6, G7, G8, G10 and G15) have been reported among BoRV-A (Matsuda et al, 1990;Blackhall et al, 1992;Brüssow et al, 1992;Isegawa et al, 1994;Fukai et al, 1999Fukai et al, , 2005Rao et al, 2000;Alfieri et al, 2004). Types G2 and G11 in BoRV-A have been detected using PCRderived cDNA probes (Hussein et al, 1993).…”
mentioning
confidence: 99%